SOCIAL MAPPING AND IDENTIFICATION OF SOCIO-ECONOMIC VULNERABILITIES OF VULNERABLE GROUPS IN URBAN AREAS (STUDY IN MEDAN CITY): PEMETAAN SOSIAL DAN IDENTIFIKASI KERENTANAN SOSIAL-EKONOMI KELOMPOK RENTAN DI KAWASAN PERKOTAAN (STUDI DI KOTA MEDAN) - Gusti Pirandy; Mujahid Widian Saragih; Farida Hanim (SOSIOEDUKASI, 2025)
This study aims to map and identify the socio-economic vulnerability of vulnerable groups in urban areas, especially in the city of Medan. With a descriptive qualitative approach, the study focuses on the collection of primary data through surveys, in-depth interviews, and FGDs. The background of this research departs from the phenomenon of social inequality that is increasingly real in the midst of rapid urbanization and the limitations of accurate micro data as the basis for the formulation of social intervention policies. The research also highlights the need for a participatory and community-based approach to development in response to the failure of elitist and top-down development models. This research is based on the need to build a data foundation that can be used by policymakers, development practitioners, and local communities in designing more effective and equitable social interventions. The city of Medan was chosen as the location because of the complexity of its social problems that represent major cities in Indonesia, including high urbanization, inequality between regions, and weak access for marginalized groups to development programs. This study will be the starting point of a ten-year long-term research series aimed at designing evidence-based and contextual models of social intervention, this research is based on the theoretical frameworks of social vulnerability, community participation and empowerment, and social intervention theory.